AN ECHOCARDIOGRPHIC REEVALUATION OF ELECTROCARDIOGRAPHIC AND VECTORCARDIOGRAPHIC PARAMETERS FOR DIAGNOSIS OF LEFT VENTRICULAR HYPERTROPHY - NAGUMO, MAKOTO (Kita Kantō igaku (The Kitakanto Medical Journal), 1988)
The electrocardiograms and vectorcardiograms of 80 cardiac patients and 51 normal subjects were quantitatively analyzed and the results were compared with the echocardiographic observations. The patient group consisted of 7 cases of hypertrophic cardiomyopathy, 19 cases of dilated cardiomyopathy, 17 cases of hypertensive heart disease and 37 cases of aortic valve disease. The routinely measured voltage parameters such as RI+ SIII, RaVL, RaVF, SV1, RV5 and Sv1 + RV5 and the magnitude of the planar maximum QRS vector all correlated positively with the left ventricular mass index, left ventricular wall thickness, interventricular septal thickness, posterior wall thickness and left ventricular diastolic dimension index. However, the measured voltages correlated much better with the indices of left ventricular mass and wall thickness than with left ventricular diastolic dimension. Thus, the enlarged QRS vectors in left ventricular hypertrophy were considered to be mainly the result of the increase in left ventricular muscular mass rather than left ventricular cavitary dilatation. On the other hand, calculation of the diagnostic sensitivity and specificity for each voltage parameter revealed that all of the above measurements were diagnostically almost equivalent : none was superior to the others. There fore, some parameters other than the QRS voltage should be included to set better criteria for the diagnosis of left ventricular hypertrophy.